Equal pay now - Funding for Local Government - stickers, 2007 (2007)
2007 1960-2000 "Equal pay now - Funding for Local Government - stickers, 2007" [EP0178], 2007 The Equal Pay Now campaign was launched in 2007 to lobby government to provide funding for local government to achieve equal pay. These stickers were used as publicity at the Lobby of Parliament on July 10, 2007, which was organized by Unison, the GMB and Unite - TGWU unions.